PEMANFAATAN ABU CANGKANG KERANG DARAH (ANADARA GRANOSA) SEBAGAI KATALIS DALAM PEMBUATAN METIL ESTER DARI MINYAK JELANTAH (Talenta Publisher (Universitas Sumatera Utara), 2015)
Transesterification is the reaction to produce methyl esters in which this reaction’s involves catalyst of blood clam shell ashes of combustion at temperatures of 900 ° C for 3 hours and the amount of ash that is used by 8%, 10%, 12% (w / w). Ash used in dissolved in methanol with a molar ratio of methanol: oil of 9: 1, 12: 1 (n / n) to obtain a compound of calcium methoxide. Used cooking oil is filtered and then esterified with catalyst 3.0% (w / w) H2SO4 98% and methanol: oil TG (6: 1) to reduce the FFA to <1%. Transesterification reaction is carried out at a reaction temperature of 65 ° C for 3 hours, and keep stirring 700 rpm. Quantitatively, the optimum yield of methyl ester in the amount of ash produced is 12% (w / w) and the molar ratio of methanol: oil at 12: 1 (n / n) of 56.51% with specification methyl esters such as density, kinematic viscosity and purity methyl ester biodiesel in accordance with SNI 04-7182-2006, based on the analysis of GC (Gas Chromatography), the purity of the resulting methyl ester was 98.79%.